A High-Order Characteristic Basis Function Algorithm for an Efficient Analysis of Printed Microwave Circuits and Antennas Etched on Layered Media - Bianconi, G.; Pelletti, C.; Mittra, R. (IEEE antennas and wireless propagation letters, 2013)
In this letter, we present a characteristic basis function method (CBFM) algorithm for an efficient "full-wave" analysis of printed microwave circuits and antennas etched on layered media. The main contribution of the proposed approach is a technique for the generation of the primary characteristic basis functions (PCBFs) in conjunction with the employment of high-order characteristic basis functions (CBFs), which enables us to implement a totally general decomposition scheme of the circuit under analysis. Numerical examples are presented to demonstrate the efficiency and the accuracy of the proposed approach.